HUBUNGAN KEJADIAN PENDARAHAN POS PARTUM DINI DENGAN PANITAS DI RSUD Dr. M. DJAMIL PADANG TAHUN 2005 - Miswarti Miswarti (Jurnal Kesehatan Masyarakat Andalas, 2007)
The post partum bleeding was a casual of serious blood lose which most commonly found in obstetrics case and was most casual of death in from all mother’s mortality case. The objectives of this research was o find out the early post partum incident in RSUD Dr. M. Djamil Padang in 2005 compare with all childbird case during 005 in RSUP Dr. M. Djamil Padang , and to find out early post partum incident in RSUP Dr. M. Dlail Padang according to the parity based on the number of early post partum bleeding in 2005. Kind of research was descriptive retrospective research with all of mother who giving birth in RSUP Dr. M. Djamil Padang which  experiences the post partum bleeding as the population. The sample was all of mother who gave birth with experiences post partum bleeding based on parity. Data was taken through data collection format. Data analysis used univariate and bivariate analysis. The result found that the post partum bleeding incident in RSUD Dr. M Djamil Padang in 2005 was 4,40% from all of the childbirth, whereas post partum bleeding was in second place of ten most obstetrics case in RSUP Dr. M. Djamil Padang. There was also found that the incident rate of 1 parity were 15 cases or 11,54 %. 2-3 parity was 52 case or 40 % and 4 or more parity was higher compare to 2-3 parity, wich are 63 case or 48,46%. Bivariate analysis found that calculate X2 > X2 table, so it can concludes that there was a significant relationship between post partum bleeding in RSUP Dr. M. Djamil Padang with parity. Researcher advising the paramedics to inform the societyto not having children more than 4, because it could increse the risks on the next childbirth which one of them is post partum bleeding.